SINERGITAS KEPEMIMPINAN DALAM PERSPEKTIF PENTAKOSTA: SEBUAH ANALISIS NARATIF HAKIM-HAKIM 4:1-24 - Hiruniko Ruben; David Michael Gerungan; Ivonne Sandra Sumual; Samuel Yosef Setiawan (Diegesis : Jurnal Teologi, 2022)
Leadership is an essential factor in the progress of a nation, organization, even church. If the leader can carry out his responsibilities, there will be a transformation, but otherwise, it will be destructive. The book of Judges describes leaders who are transformative but also destructive. This study aims to analyze the leadership of the Pentecostals from the point of view of Judges chapter 4. The research method used is a narrative analysis of the text of Judges 4:1-24. The study results show that synchronizing the text of Judges 4:1-24 will increase the importance of the role of leaders to make people aware of divine support, which not only strengthens them when they are weak but also equips sharpens their "weapons" to achieve victory. The primary key lies in the desire to cooperate in God's agenda by working together and hand in hand to accomplish God's purposes and plans in our generation.